Perancangan Typeface Adaptasi Dari Motif Rumpun Biluluk Kabupaten Aceh Barat Daya - Ampoen Fachrial; Harissman (VisArt: Jurnal Seni Rupa dan Design, 2026)
The design of a typeface adapted from the rumpun biluluk motif represents an effort to preserve the culture of Southwest Aceh through the medium of typography. The rumpun biluluk motif, inspired by the traditions of manoe pucok and the pho dance, is modified into visual elements of letters to create a new identity in the field of typography. This research employs a qualitative method through literature study, observation, and 5W+1H analysis. The design process encompasses idea synthesis, form exploration, stylization, manual sketching, digitization using Adobe Illustrator, and font programming with FontLab. The resulting typeface, named Rumbiya Typeface, is categorized as a display typeface in OTF (OpenType Font) format, which can be utilized across various digital devices. Rumbiya Typeface functions not only as a graphic design work but also as a cultural preservation strategy, reinforcing the existence of the rumpun biluluk motif and opening opportunities for its application in communication media and creative products. Thus, this work is expected to serve as a new visual identity that represents the cultural richness of Southwest Aceh